Large scale Data Sharing using BestPeer++ Technique (International Journal of Engineering and Computer Science, 2015)
The corporate network those are working in same sector needs to share information frequently and facilitates collaboration. Certain companies with common interest  eﬀectively shares data to reduce operational cost and increases revenues. In this Project, we develop a system which provides functionality among these companies to share data with security , scalability, high performance and high throughput .It also provides elastic data sharing among these companies in a network Based P2P data management with the help of Bootstrap peer. Bootstrap peer acts as a entry point for join and departure of nodes and it also provides access control to those peer and also it manages metadata of whole network .By integrating data base and P2P technology, BestPeer++  gives low cost, ﬂexible and scalable platform for data sharing.